2003
DOI: 10.1182/blood-2002-10-3310
|View full text |Cite
|
Sign up to set email alerts
|

A 6-month versus a 12-month surveillance for hepatocellular carcinoma in 559 hemophiliacs infected with the hepatitis C virus

Abstract: Hepatocellular carcinoma (HCC) is an increasingly frequent cause of mortality in hemophiliacs with chronic viral hepatitis. Early diagnosis of the tumor at an initial stage is known to improve the outcome of HCC treatment. Because all HCC cases detected in a previous study based upon annual ultrasound (US) surveillance of hemophiliacs with elevated alanine aminotransferase levels were multinodular, this study was designed to evaluate if a more intense surveillance with US and alphafetoprotein (AFP) serum level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
61
1
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(65 citation statements)
references
References 28 publications
1
61
1
2
Order By: Relevance
“…148 Another study in HCV infected hemophiliacs without cirrhosis suggested that the likelihood of finding HCC at the single nodule stage (as opposed to multinodular HCC) was the same with 6 and 12 month surveillance intervals. 149 Thus, the surveillance interval remains controversial. Most experts use a 6-month interval, but there are no firm data to suggest that 6 months is better than 12 months.…”
Section: Surveillance Intervalmentioning
confidence: 99%
“…148 Another study in HCV infected hemophiliacs without cirrhosis suggested that the likelihood of finding HCC at the single nodule stage (as opposed to multinodular HCC) was the same with 6 and 12 month surveillance intervals. 149 Thus, the surveillance interval remains controversial. Most experts use a 6-month interval, but there are no firm data to suggest that 6 months is better than 12 months.…”
Section: Surveillance Intervalmentioning
confidence: 99%
“…In contrast, the guidelines proposed by the American Association for study of Liver Diseases (AASLD) proposes that US be performed at 6-month intervals for all patients at risk of HCC regardless of the magnitude of risk but based on expected tumour doubling times. Although the retrospective study by Zhang et al used a surveillance interval of 6 months, [7] several other studies report that the likelihood of finding HCC at the single nodule stage is no different between 6-and 12-month surveillance intervals [12,13]. One nonrandomised prospective study in patients with hepatitis B has demonstrated that survival is greater when surveillance intervals are shortened to 6 months as opposed to 12 months [14].…”
mentioning
confidence: 99%
“…A prospective cohort study found that patients with HBV had a better survival with a surveillance interval of 6 months than with 12 months (45). However, other studies have found no significant differences in survival or the rate of HCC detection with intervals of 6 and 12 months (46,47). Of the 18 guidelines that were reviewed here, 8 tended to recommend a surveillance interval of 6 months and 2 recommended an interval of 6 to 12 months.…”
Section: High-risk Population and Surveillance Of Hccmentioning
confidence: 99%